Family members' experiences of caring for a relative with substance-induced psychosis disorder - Sanny Selotole; Annie Temane; Marie Poggenpoel (AOSIS, 2022)
Background: When there is a lack of resources in the community to support deinstitutionalisation, family members of a relative diagnosed with substance-induced psychosis disorder (SIPD) are the most affected and vulnerable. Nevertheless, family members' care is still largely unacknowledged in the mental health sector in low- and middle-income countries. Furthermore, no prior research could be found on family members' experiences caring for a relative with SIPD in Giyani, Limpopo province, South Africa. Objectives: To explore and describe family members' experiences caring for a relative with SIPD. Method: The study employed a qualitative research design using interpretative phenomenological analysis as the research method. Telephonic interviews were conducted and analysed. Eight family members were selected to participate in the study using a purposive sampling technique. Results: The analysis of data led to the emergence of the following themes: family members experienced caring for a relative with SIPD as a destabilising responsibility; they experienced acceptance and support from significant others and the community and solace in prayer. Participants also expressed they experienced a need for support from government structures in order to care for a relative with SIPD. Conclusion: The study's findings highlighted the family members' experiences of caring for a relative with SIPD and the role of the family, community and government structures in caring for an individual with SIPD. It is evident from the challenges experienced that the family members need external interventions to develop healthy coping strategies. Contribution: This study adds knowledge to nursing practice, nursing education and nursing research by promoting effective coping amongst family members caring for a relative with SIPD.